Hydrothermally Synthesized Cobalt Borophosphate as an Electrocatalyst for Water Oxidation in the pH Range from 7 to 14. Issue 12 (24th June 2019) - Ülker, Emine
Abstract: The synthesis of earth‐abundant‐metal‐based, robust, efficient and cost‐effective water oxidation electrocatalysts is necessary for renewable energy conversion processes. In this study, a crystalline cobalt borophosphate (CoBP) was synthesized by reacting CoCl2 .6H2 O with B2 O3 and (NH4 )2 HPO4 and evaluated as an electrocatalyst for water oxidation catalysis. The electrochemical and electrocatalytic performance of the catalyst towards water oxidation has been investigated by catalyst coating on fluorine doped tin oxide (FTO) electrode in different pH solution. Cyclic voltammetric and chronoamperometric studies were performed for the investigation of pH effect on the catalytic activity. Post‐catalytic studies indicate that CoBP acts as a pre‐catalyst yielding an active phase during the course of electrolysis in the alkaline conditions. The catalyst demonstrated catalytic activity at pH 13.6 with onset potential of 1.46 V (vs. RHE) and Tafel slope of 57 mV dec −1 . Electrochemical studies show that catalyst exhibits a current densities of 1 and 10 mA cm −2 at 384 and 441 mV. The catalyst showed a turnover frequency (TOF) of 1.1×10 −2 s −1 at overpotential of 300 mV. Abstract : The electrocatalytic water oxidation performance of a crystalline cobalt borophosphate compound is investigated at different pH values